PENGARUH KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN DENGAN PENGUNGKAPAN CSR DAN GCG SEBAGAI VARIABEL PEMODERASI - Hidayatullah (Media Riset Akuntansi, Auditing & Informasi, 2010)
This Thesis investigated the influence of financial performance toward corporate value by exposing Corporate Sosial Responsibility (CSR) and Good Corporate Governance (GCG) as Moderating Variables. Corporate Financial performance as independent variable is represented by the Financial Value Added (FVA) and Corporate Value as Dependent Variable is represented by Tobin `s Q value. CSR value is indexed based on the 78 items of exposure themes and GCG value is indexed using the 18 items of exposure themes which the researcher called Corporate Governance Perception Index. After selecting 149 companies listed in Indonesia Stock Exchange, the researcher found 39 manufacture companies.  qualified as the research objects based on the defined criteria, with observation timeframe from the year of2005 to 2008. The result of the research concludes that: Financial Performance (FVA) significantly influences the corporate value (Tobins 'Q); Corporate Sosial Responsibility also influences the relationship of corporate financial performance and the corporate value; and Good Corporate Governance influences the relationship of corporate financial performance and the corporate value as well.Keywords: Financial value Added, Tobin 's Q, CSR, GCG